ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Sulistyani, Sulistyani; Ismanto, Deny (Jurnal Fokus Manajemen Bisnis, 2017)
Financial  distress  precedes  bankruptcy.  Most  financial  distress  models actually rely on bankruptcy data, which is easier to obtain. The purpose of this research to examine financial ratios that predict financial distress condition of a firm. The sample of this research consist of 14 distress firm and 79 non-distress firms, chosen by purposive sampling. The statistic method which is used to test on the research hypothesis  is logistic regresion. The results show that the liquidity ratio (current assets/current liabilities) and a leverage ratio  (current leabilities/total  asset)  is  a  significant  variable  to  determine  of  financial  distress firms.  When  profitability  ratio  (net  income/net  sales)  and  price  earning  ratio (market  price  per  share/earnings  per  share)  are  not  significant  variables  to determine of financial distress.